2021
DOI: 10.3389/fmicb.2021.691842
|View full text |Cite
|
Sign up to set email alerts
|

Identification of LuxR Family Regulators That Integrate Into Quorum Sensing Circuit in Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus is one of the most important food-borne pathogens that cause economic and public health problems worldwide. Quorum sensing (QS) is a way for the cell-cell communication between bacteria that controls a wide spectrum of processes and phenotypic behaviors. In this study, we performed a systematic research of LuxR family regulators in V. parahaemolyticus and found that they influence the bacterial growth and biofilm formation. We then established a QS reporter plasmid based on bioluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In the V. fisheri QS system, autoinducers (AIs) and two essential proteins (LuxR and LuxI) regulate bioluminescence signal production. The LuxI enzyme produces the QS signal molecule (the N-3-oxo-hexanoyl-homoserine lactone), and LuxR is a transcription regulator that binds to the AHL signal and regulates bioluminescence via the luxCDABEG operon [ 9 ]. Following the discovery of the AHL-QS system, researchers discovered that AHL-QS is prevalent in a wide range of Proteobacteria and influences vital characteristics such as motility [ 10 ], pigment production [ 11 ], and biofilm formation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the V. fisheri QS system, autoinducers (AIs) and two essential proteins (LuxR and LuxI) regulate bioluminescence signal production. The LuxI enzyme produces the QS signal molecule (the N-3-oxo-hexanoyl-homoserine lactone), and LuxR is a transcription regulator that binds to the AHL signal and regulates bioluminescence via the luxCDABEG operon [ 9 ]. Following the discovery of the AHL-QS system, researchers discovered that AHL-QS is prevalent in a wide range of Proteobacteria and influences vital characteristics such as motility [ 10 ], pigment production [ 11 ], and biofilm formation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…V. parahaemolyticus is recognized as a new species because of vibriosis related to the consumption of contaminated raw or undercooked seafood ( Ashrafudoulla et al, 2021 ). Sepsis has also been reported when wounds were exposed to the pathogen ( Zhong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the functions of these three QS sensor‐autoinducer pairs of V. parahaemolyticus , we first constructed deletion mutants in each of the genes and transformed a reporter plasmid containing the bioluminescence luxCDABE operon cloned from V. harveyi (Zhong et al, 2021) into all these mutants. By testing light production of the bioluminescence reporter in these mutants, we found that the mutants of Δ opaR and Δ cqsA vp /Δ luxM vp /Δ luxS vp (hereafter referred to as Δ3AI) could not produce light (Figure 2b), which indicated that the luxCDABE operon from the reporter plasmid could only be activated by OpaR in the presence of the signals synthesized by CqsA vp , LuxM vp , and LuxS vp .…”
Section: Resultsmentioning
confidence: 99%